Intention to use ChatGPT among law educators in Saudi Arabia - Sarabdeen, Jawahitha (Frontiers in Education, 2025)
ChatGPT empowers instructors to provide interactive, individualized attention and enhance student engagement. It is used to understand the learners so that the teaching materials and assessments can be contextualized. ChatGPT can enrich the learning experience, motivate the learners, and improve academic performance. No study in Saudi Arabia surveyed law educators on the intention to use ChatGPT. To fill the gap in this area, this research investigated the intention of law educators to use ChatGPT. To achieve the research objective, the researcher used a survey method to collect information from law educators in Saudi Arabia. The research revealed that law educators will use ChatGPT in legal education as the constructs of the performance expectancy, effort expectancy, social influence, facilitating conditions, and behavioral intention are found to be significant. The finding has policy, practical, and theoretical implications. The finding can be used to understand the factors that influence ChatGPT adoption by law educators. Accordingly, teaching and learning policies can be strengthened, and the learning institutions can introduce training for the proper and acceptable use of ChatGPT in legal education. The research also expanded the technology adoption model to understand the intention to use ChatGPT among law educators in a developing country.